PERALIHAN HAK ATAS TANAH ADAT MELALUI HIBAH DALAM SISTEM MATRILINEAL MINANGKABAU DIHUBUNGKAN DENGAN PERATURAN PEMERINTAH NOMOR 24 TAHUN 1997 TENTANG PENDAFTARAN TANAH - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2010)
The research aims to identify and understand the position of Surat Hibah (grant letter) on hibah tanah adat (customary land grant) in Minangkabau matrilineal system related to the Government's Regulation Number 24 in The Years of 1997 on Land Registration, and to identify and understand to what extent the Government's Regulation Number 24 in The Years of 1997 on Land Registration to protect the beneficiaries of customary land grant, when registration is not conducted. This research on the right conversion of customary land under grant mechanism in the Minangkabau matrilineal system related to the Government's Regulation Number 24 in The Years of 1997 on Land Registration adopts juridical empiris legal research method, i.e. a legal research conducted through literature reviews to obtain secondary data, and followed with field studies to collect primary data. The Padang Municipality and Solok district of West Sumatera province are preferred as research sites. Research populations involve Minangkabau communities with 5 (five) samples taken from those conducting customary land right conversion under grant mechanism in Minangkabau matrilineal system, and 1 (one) Public Notary, 2 (two) Chief ofKerapatan Adat Nagari (KAN), and 1 (one) Wali Nagari Nagari, also took as the other respondent.Data collection is conducted through interviews and documentary study. According to the research is concluded that the position of grant letter in the customary land grant in Minangkabau matrilineal system, is recognized as a legal deed, based on the Government's Regulation (PP) Number 24 in The Years of 1997 on Land Registration. The existence of grant letter in land grant under the Minangkabau customary law is used as the basis for right conversion on customary land. Legal protection for the beneficiary of customary land grant, particularly in Minangkabau, is also endowed with the PP Number 24 in The Years of 1997 on Land